(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
In the article copper-porphyry ore fields uncovered by varying degrees of erosion are described. On eroded Dastakert ore field copper-porphyry mineralization is opened, but on Arevis less eroded part, accompanying gold-sulphide mineralization is preserved. Within the first ore field the two different age copper-porphyry mineralizations are manifested.